Liberalisation of Banking Services Under the Framework of Asean Economic Community: an Indonesian Perspective - Nandang Sutrisno; Nur Gemilang Mahardhika (Hang Tuah Law Journal, 2022)
Among the ASEAN members, compared to other members, Indonesia is relatively more liberal in opening up international trade in financial services, especially in banking sector. Through its submission of CIO to the WTO in 2005, Indonesia to some degree offered certain liberalization of banking sector, together with some other services governed under the GATS. On the other hand, other members of ASEAN show their carefulness in liberalizing their banking sectors. As consequence, on one hand foreign banks have occupied nearly 50% of the Indonesian banking industry, and there are only a few units from Indonesia’s domestic banks that present in its ASEAN neighbours, on the other hand. Using normative method, this research elaborates on how Indonesia should strike a balanced stand between its over-liberalized banking sector and the reluctance of other members, while maintaining the GATS principle of “progressive development.” The authors concludes that one of the ways for Indonesia to flip the odds to be in its favour is by urging the implementation of the reciprocity principle in banking services in ASEAN, which additionally, will also stimulate the liberalisation schedule of the latter.